Diversification of Dairy Cow Milk Products: Case Studies in Sendang Village, Tulungagung Regency - Utomo, Pamuji Setyo; Sosiawati, Endang Sapta Hari; Fauziyah, Fauziyah (Prosiding Seminar, 2020)
Productivity of dairy farmers in Sendang Village could be done through coaching and training to dairy farmers in Sendang Village through the application of science and technology needed by dairy farmers, namely by providing pasteurization tools to process milk into various beverage products and products ready to be marketed. The expected targets and outputs in the PKM program are better management pattern system and a better accounting system, and Products produced (Beverage Flavored Milk Beef, Cheese, Ice Sticks, and Various Ice Cream Flavors). The steps taken in the community service program are dissemination to members of the cattle ranchers group regarding the benefits and benefits of management and production in the manufacture of milk beverage products; providing education and training on how to use pasteurization tools to process milk into a beverage product that has various flavors; and assistance creating product layouts, management training, accounting and marketing. The conclusions are the group of trained farmers have been able to carry out managerial activities in the business of making fresh milk-based food and beverage products; the group has been able to make a production layout, calculate the production costs and make a profit and loss statement and make a financial balance sheet report on the processing; the livestock groups have been able to plan the intended market and are able to determine the products to be marketed in a large capacity; and provision of production equipment assistance has increased the entrepreneurial capacity of dairy farmers in Sendang Village, Tulungagung Regency.